Attribution of the heavy rainfall events leading to severe flooding in Western Europe during July 2021 - Jordis S. Tradowsky; Sjoukje Y. Philip; Frank Kreienkamp; Sarah F. Kew; Philip Lorenz; Julie Arrighi; Thomas Bettmann; Steven Caluwaerts; Steven C. Chan; Lesley De Cruz; Hylke de Vries; Norbert Demuth; et al. (Climatic Change, 2023)
In July 2021 extreme rainfall across Western Europe caused severe flooding and substantial impacts, including over 200 fatalities and extensive infrastructure damage within Germany and the Benelux countries. After the event, a hydrological assessment and a probabilistic event attribution analysis of rainfall data were initiated and complemented by discussing the vulnerability and exposure context. The global mean surface temperature (GMST) served as a covariate in a generalised extreme value distribution fitted to observational and model data, exploiting the dependence on GMST to estimate how anthropogenic climate change affects the likelihood and severity of extreme events. Rainfall accumulations in Ahr/Erft and the Belgian Meuse catchment vastly exceeded previous observed records. In regions of that limited size the robust estimation of return values and the detection and attribution of rainfall trends are challenging. However, for the larger Western European region it was found that, under current climate conditions, on average one rainfall event of this magnitude can be expected every 400 years at any given location. Consequently, within the entire region, events of similar magnitude are expected to occur more frequently than once in 400 years. Anthropogenic climate change has already increased the intensity of the maximum 1-day rainfall event in the summer season by 3–19 %. The likelihood of such an event to occur today compared to a 1.2 $$^{° }$$ ∘ C cooler climate has increased by a factor of 1.2–9. Models indicate that intensity and frequency of such events will further increase with future global warming. While attribution of small-scale events remains challenging, this study shows that there is a robust increase in the likelihood and severity of rainfall events such as the ones causing extreme impacts in July 2021 when considering a larger region.

Hochwasserfrühwarnung in Rheinland-Pfalz - Margret Johst; Norbert Demuth (WASSERWIRTSCHAFT, 2022)

Hochwasserfrühwarnung - gemeinsamer Beitrag aus Sachsen und Rheinland-Pfalz - Norbert Demuth; Andy Philipp (WASSERWIRTSCHAFT, 2018)